Research progress of iron-based catalysts for selective oligomerization of ethylene. Issue 71 (8th December 2020) - Wang, Mingzhi; Wu, Wei; Wang, Xu; Huang, Xing; Nai, Yongning; Wei, Xueying; Mao, Guoliang
Abstract : In this paper, the research progress of catalysts for selective oligomerization of ethylene was reviewed in terms of the cocatalysts, ligand structure, oxidation state of the iron metal atom center and immobilization of homogeneous catalysts. Abstract : Linear α-olefins are widely used as raw materials in the chemical industry. Selective ethylene oligomerization is an important development direction of the linear α-olefin production process. Iron-based catalysts have become a research hotspot in selective ethylene oligomerization due to their advantages like high activity, high selectivity and convenience of adjusting their ligand structures. In this paper, the research progress of catalysts for selective oligomerization of ethylene was reviewed in terms of the cocatalysts, ligand structure, and immobilization of homogeneous catalysts.